STRUCTURAL-SEMANTIC METHODS OF INTRODUCTION TO HISTORICAL MONUMENTS IN CHINESE-UZBEK TOURIST DISCOURSE - Vakhabova Niginabonu Jurabekovna (Western European Studies, 2024)
This article discusses structural-semantic methods of introduction to historical monuments in the Chinese-Uzbek tourist discourse. Culture and translation are closely related to each other. Tourism itself demonstrates widespread cultural communication in that sense. Therefore, in order to facilitate communication between different cultures, the translator must handle cultural elements in tourism materials accordingly. Among these cultural characteristics of tourism materials, cultural gap is one of the most obvious characteristics that occupy a large part in the translation of tourism materials.
Keywords: methods; translation; Chinese language; Uzbek language